Non-host Resistance: DNA Damage Is Associated with SA Signaling for Induction of PR Genes and Contributes to the Growth Suppression of a Pea Pathogen on Pea Endocarp Tissue - Hadwiger, Lee A.; Tanaka, Kiwamu (Frontiers in Plant Science, 2017)
Salicylic acid (SA) has been reported to induce plant defense responses. The transcriptions of defense genes that are responsible for a given plant's resistance to an array of plant pathogens are activated in a process called nonhost resistance. Biotic signals capable of carrying out the activation of pathogenesis-related (PR) genes in pea tissue include fungal DNase and chitosan, two components released from Fusarium solani spores that are known to target host DNA. Recent reports indicate that SA also has a physical affinity for DNA. Here, we report that SA-induced ROS release results in fragment alterations in pea nuclear DNA and cytologically-detectable diameter and structural changes in the pea host nuclei. Additionally, we examine the subsequent SA-related increase of resistance to the true pea pathogen Fusarium solani f.sp. pisi and the low accumulation of the phytoalexin pisatin. This is the first report showing that SA-induced PR gene activation may act directly on the host pea genomic DNA and that at certain concentrations, SA can be temporally associated with subsequent increases in the defense response of this legume.